Variability And Character Association In Bangladhonia (Eryngium foetidum L.) (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted at the Horticulture Field Laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during November 2005 to July 2006. Twelve genotypes of Bangladhonia (E. foetidum L.) were collected from different parts of Bangladesh and evaluated them to analyze the variations. Most of the yield attributing characters and individual plant performances exhibited insignificant differences among the genotypes. All the genotype had the similar plant and leaf size, number of leaves/plant, weight of leaves/plant, flowering behavior, yields and other qualitative characters. Greater positive correlation was observed between plant populations with yield performances. The symmetric performance indicted that all the genotype belongs from the same species of E. foetidum L. and there was no major phenotypic or genotypic variation among them. Bangladesh J. Agril. Res. 38(1): 77-84, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15192